Prototype of a Dust Monitoring Device in the Mechanical Engineering Laboratory at PGRI University Semarang Using the GP2Y1010AU0F Sensor - Rifki Hermana; Muchamad Malik; Agus Mukhtar; Andrew Joewono; Gostsa Khusnun Naufal (Jurnal Engine: Energi, Manufaktur, dan Material, 2024)
ABSTRACT This study aims to develop an accurate and real-time air quality monitoring system in the Mechanical Engineering Laboratory that provides information on the measured parameter values. The research employs an experimental approach to determine the effectiveness of variables within the experiment. The primary sensor used is the GP2Y1010AU0F Optical Dust Sensor, which operates based on infrared light to measure particulate dust concentration levels. Analysis of sensor testing results was conducted by observing variations in sensor readings, notably after trials involving tissue burnt as a dust source. The dust sensor consistently recorded an average dust concentration of 0.597 Kg/m³. Subsequently, tests were conducted using baby powder with a constant weight of 30 mg per trial. Sensor readings varied between 0.35 Kg/m³ and 0.38 Kg/m³, indicating that within the given weight range, the powder mass does not significantly impact sensor readings. Further, tests on indoor dust density, with an average concentration of 36.01 µg/m³, revealed a relatively low average dust concentration in the room during the measurement period..